Alocação de risco de demanda em concessões de rodovia - Rangel, Maria Caroline dos Santos (2017)
Any project requiring human cooperation is subject to divergence interests among parties, which can clearly be observed in infrastructure projects. In modern societies, conflicts of interest are usually mitigated by contractual arrangements, in which, if well delineated, provide the right incentives for cooperation. However, contracts are incomplete, especially those of road concessions, characterized by their long duration and high investments, and therefore they are subject to risks. In this scenario of uncertainties, one of the main risks is the demand risk, i.e., the risk of volume of traffic carried out is lower than projected, affecting the continuity and profitability of the project. Therefore, the present evaluates who should bear the risk of demand in road concessions in Brazil: a private entity, which currently supports this risk, a public entity, or both (shared). To answer this question, the Incentive Theory, together with several international case studies, have been analysed. The presente paper categories the need to transfer risk from private to public administration according to the degree of risk criteria, such as demand risk and risk aversion.